2015
DOI: 10.1099/mic.0.000068
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of coffee-infecting Xylella fastidiosa strains isolated from Brazil

Abstract: Strains of Xylella fastidiosa constitute a complex group of bacteria that develop within the xylem of many plant hosts, causing diseases of significant economic importance, such as Pierce's disease in North American grapevines and citrus variegated chlorosis in Brazil. X. fastidiosa has also been obtained from other host plants, in direct correlation with the development of diseases, as in the case of coffee leaf scorch (CLS) -a disease with potential to cause severe economic losses to the Brazilian coffee ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…As the MLSA and MLST analyses revealed that the two coffee-infecting strains were phylogenetically distant and distinct from previously described CLSrelated strains (16,55) Phylogenetic analysis of CFBP 8072 and CFBP 8073 based on genomic data. Based on these data, an entire genome-based phylogenetic tree was built using CV-Tree (44) by comparing protein sequences predicted from annotation analysis performed on CFBP 8072 and CFBP 8073 to 17 publicly available predicted proteomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the MLSA and MLST analyses revealed that the two coffee-infecting strains were phylogenetically distant and distinct from previously described CLSrelated strains (16,55) Phylogenetic analysis of CFBP 8072 and CFBP 8073 based on genomic data. Based on these data, an entire genome-based phylogenetic tree was built using CV-Tree (44) by comparing protein sequences predicted from annotation analysis performed on CFBP 8072 and CFBP 8073 to 17 publicly available predicted proteomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The genome sequences of the following four X. fastidiosa strains that were isolated from coffee plants are available: CFBP 8072 isolated from C. arabica originating from Ecuador, CFBP 8073 isolated from C. canephora originating from Mexico, and strains 6c and 32 (isolated from Coffea spp. from Brazil) (55,58). To identify potential determinants of coffee plant adaptation, we compared these genome sequences to the 13 other available X. fastidiosa genome sequences representing X. fastidiosa strains which are not known to infect coffee plants (Table 3, excluding the PLS 229 strain that does not belong to X. fastidiosa).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By whole genome approach, the complete set of unique genes present in each strain can be characterized, together with those that are common to all strains (Bhattacharyya et al, 2002; Barbosa et al, 2015). Sets of genes involved in important functions can be compared and studied (da Silva et al, 2007; Barbosa et al, 2015), SNPs can be identified and PCR primers can be designed for the identification of specific strains (Doddapaneni et al, 2006; Marcelletti and Scortichini, 2016b) and detailed phylogenetic analysis can be performed. As an example, by genome-wide comparison of 21 X. fastidiosa strains, Marcelletti and Scortichini (2016a) constructed a phylogenetic tree analyzing 820,088 nucleotides, ~30% of the entire X. fastidiosa genome.…”
Section: Hosts and Diseasesmentioning
confidence: 99%